Puetz-Jeghers Syndrome Involving Appedix - Al-Fayadh, Raysan F.; Awad, Ali Jaliel (AL-Kindy College Medical Journal, 2010)
This is an autosomal dominant disease. The gene STK11 on chromosome 19 has been found in proportions of patients with this condition, this consists of: A-Intestinal hamartomatosis. B-Melanosis of the oral mucous membrane and the lips.